IMPLEMENTASI PELATIHAN MANAJEMEN DANA DESA UNTUK MENINGKATKAN KAPASITAS PEMBERDAYAAN DI DESA LAKSANAMEKAR - Rivaldo; Mulyono, Dinno (Comm-Edu (Community Education Journal), 2025)
Village fund management training is important because it can provide village stakeholders with the necessary knowledge and skills to manage village funds effectively and efficiently. This research will explore how this training can increase community empowerment capacity in Laksanamekar Village. The theoretical basis used in this research is training theory, village fund management theory and community empowerment theory. The research method uses qualitative methods with data collection including observation, interviews and documentation to gain a comprehensive understanding of the implementation of the training and its impact on the local community. There were 6 respondents,the results of this research in Laksanamekar village show the importance of fund management training to increase community empowerment capacity. The implementation of village fund management training which was attended by village officials had an impact on village institutions and RW heads because with good village fund management the community empowerment capacity in Laksanamekar village could be further increased. Then the conclusion of this research is that the implementation of village fund management training is expected to provide benefits for the Laksanamekar village government and the Laksanamekar village community both regarding the effectiveness of village fund management training in increasing community empowerment capacity, as well as providing recommendations for the government and related organizations to improve the implementation of training in the future.